Motivational and cognitive value of games in the teaching process - Nikolić, Sanja S.; Saračević, Muzafer H.; Šabotić, Mirela S. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2020)
It has long been recognized that learning content is very useful for developing the intellectual and creative abilities of children. Modern teaching requires dynamic, diverse teaching and its a-daptability to the abilities of each individual student. This implies a skillful combination of modern teaching materials, methods, forms and the choice of teaching form in each lesson. In that context, motivational games in the class have a special function. It is common knowledge of every teacher that students in classes need to be encouraged towards full engagement of cognitive abilities. This is not always easy to achieve. In every class, psychological preparation (application) is necessary to mobilize students' attention in the shortest possible period of time, prepare them for cognitive activities, whether it is preparation for the processing of new teaching contents, doing exercises or repeating old material. In all this, well selected motivational games can play a significant role. With engagement of cognitive process in solving such tasks, students can find successful solutions in a short time, and success is the best motive for further work in class.
Keywords: motivation; learning; teaching process; play; didactic-motivational play